2019
DOI: 10.1111/cmi.13107
|View full text |Cite
|
Sign up to set email alerts
|

Here, there, and everywhere: How pathogenicEscherichia colisense and respond to gastrointestinal biogeography

Abstract: Gastrointestinal (GI) pathogens enteropathogenic and enterohaemorrhagic Escherichia coli (EPEC and EHEC), and related mouse pathogen Citrobacter rodentium, are referred to as attaching and effacing (AE) pathogens for the lesions they form upon colonisation of the host epithelium. EPEC, EHEC, and C. rodentium are well known to use a type III secretion system to intimately attach to intestinal cells and secrete bacterial effectors to manipulate host cell processes. Less well known is the ability of AE pathogens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 136 publications
0
19
0
Order By: Relevance
“…The molecular obstacle(s) that make polarized non-transformed IECs more challenging to invade than typical cell lines constitutes an intriguing area for further enquiry. The prolonged bacterial attachment also suggests an additional biologically relevant epithelial colonization stage in the infection cycle of Salmonella , in apparent analogy to attaching-effacing enteropathogens that use the epithelial surface as a primary colonization niche (60).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular obstacle(s) that make polarized non-transformed IECs more challenging to invade than typical cell lines constitutes an intriguing area for further enquiry. The prolonged bacterial attachment also suggests an additional biologically relevant epithelial colonization stage in the infection cycle of Salmonella , in apparent analogy to attaching-effacing enteropathogens that use the epithelial surface as a primary colonization niche (60).…”
Section: Discussionmentioning
confidence: 99%
“…Oligonucleotide primers used in this study. 1 All primers were designed in this study except for pNLP10_F/R (21) 2 Restriction sites are underlined, enzymes indicated in primer name.…”
Section: Table S3 Average Cps/od600 Of Three Biological Replicates 1-hour Post-resuspension In Lbmentioning
confidence: 99%
“…and high-glucose DMEM with MOPS for cpxP-, yebE-, ygiB-, bssR-, and htpX-lux reporter plasmids. 1 Values (CPS/OD600) are the same as those represented in Figure 1A 2 P-value indicates significant difference between wild-type and ΔcpxRA mutant cells grown in the same condition (LB or HG-DMEM), Student's t-test Reporter activity was plotted relative to OD600, and data represents the mean and standard deviation of three biological replicate cultures.…”
Section: Table S3 Average Cps/od600 Of Three Biological Replicates 1-hour Post-resuspension In Lbmentioning
confidence: 99%
“…Importantly, the transcription of LEEassociated genes is known to be extensively regulated by distinct transcriptional regulators such as Ler and specific environmental conditions (temperature, pH, iron, ammonium, calcium, bicarbonate, quorum-sensing signaling etc.) [5,6,8]. The other major EHEC virulence factor is the Shiga toxin Stx.…”
Section: Introductionmentioning
confidence: 99%